Use of matrix metalloproteinase-9 (MMP-9) and its tissue inhibitor (TIMP-1) in the pathomorphological diagnosis of carotid pathology: literature review and own observations - Yu. I. Kuzyk (Zaporozhye State Medical University, 2016)
Matrix metalloproteinases (MMPs) are the degradative enzymes of the extracellular matrix. Currently, the role of MMP-2 and MMP-9 in the progression of atherosclerosis (AS) is proved. The question of possible involvement of MMP-9 into elastin degradation in fibromuscular dysplasia (FMD) and pathological tortuosity (PT) remains open and insufficiently explored. The aim of the study - analysis of the current literature on the role of degradative enzymes in the development of carotid pathology and study of the expression of type I, III, IV collagens, MMP-9 and TIPM-1 in the wall of the carotid arteries in FMD, PT and AS. Materials and methods included literature review and own research. Immunohistochemical study of type I, III and IV collagens, TIMP-1 and MMP-9 was carried out on surgical material of patients with main carotid diseases: three observations with AS, two - with FMD, two - with PT. The level of expression was assessed by semiquantitative method. Results. Own observations showed that in FMD types I and III collagen content in the media and in the adventitia remains unchanged. MMP-9 expression level reached the highest level of intensity in atherosclerotic plaques, particularly in macrophages, constituting the main part of the atheromatous mass. Moderate intensity of expression is noted in FMD and PT. In PT expression prevailed in the lower third of the media on the border with adventitia, including the adventitia, in FMD - mainly in the media. The level of TIMP-1 is weakly positive in PT and FMD, negative in AS. Conclusions. These results demonstrate the possibility of using MMP-9 and TIMP-1 as a morphological marker determining pathological processes in carotid pathology. Data of immunohistochemical study of type I, II, IV collagens indicate moderate expression of collagen type I in FMD and PT, severe expression of collagen III in FMD, moderate in PT. Type IV collagen is highly expressed in atherosclerotic plaques. For AS high expression of MMP-9 in atherosclerotic plaques is characteristic. In cases of nonatherosclerotic diseases - FMD and PT - expression intensity was moderate. MMP-9 expression level was correlated with the level of TIMP-1 - weakly positive in PT and FMD, negative in AS.